High‐Energy‐Density Chelated Chromium Flow Battery Electrolyte at Neutral pH. Issue 19 (1st September 2022) - Robb, Brian H.; Waters, Scott E.; Marshak, Michael P.
Abstract: High‐concentration operation of redox flow batteries (RFBs) is essential for increasing their energy‐storage capacity, but non‐acidic electrolytes struggle to achieve the high concentrations of metal ions dissolved in acid, limiting the development of energy‐dense neutral pH electrolytes. We report neutral pH RFB operation of chromium 1, 3‐propylenediaminetetraacetate (CrPDTA) at concentrations of 1.2 M at room temperature and 1.6 M at 40 °C, demonstrating 60% higher negolyte capacity, up to 42.9 Ah L −1, than previously reported for non‐additive‐utilizing solutions of this promising material. With extended full cell cycling, we demonstrate the importance of buffer selection and pH when using the Fumasep E‐620(K) membrane. Finally, we expand the pH operation range of CrPDTA to pH 7, which when cycled at 100 mA cm −2 against a ferrocyanide posolyte demonstrated excellent coulombic efficiencies >99.7% and energy efficiencies >87%, while operating at almost 700 mV more negative than the thermodynamic hydrogen evolution window. Abstract : Aqueous redox flow batteries utilizing a chelated chromium negative electrolyte are demonstrated. Buffer compatibility with Fumasep E‐620(K) membranes is investigated, and high‐concentration and neutral pH flow battery operation is performed. This study demonstrates that high‐energy‐density flow battery negative electrolytes at neutral pH are possible through a metal‐chelate approach.